Knowledge and Attitudes about Breast Self-Examination (BSE) in Women of Childbearing Age (WCA) in Sigulang Village, Padangsidimpuan District - Dewi Aminasty Siregar; Elvi Suryani (International Journal of Public Health Excellence (IJPHE), 2022)
According to the World Health Organization (WHO) 8-9% of women will experience breast cancer, this makes breast cancer the most common type of cancer in women. The purpose of this study was to determine "the relationship between knowledge and attitudes about breast self-examination (BSE) in women of childbearing age (WCA) in Sigulang Village". This research is descriptive in which a sample of 30 respondents obtained using a questionnaire was processed by editing, coding, tabulating, scoring and then presented in the form of a frequency distribution table. From the research results obtained frequency distribution based on the knowledge of the majority of less knowledgeable 24 respondents (80%). Based on the age, the majority of respondents lack knowledge of 21 (69 ,72 %) with the age of 20-40 years. Based on education, the majority of respondents lack knowledge of 18 (60%) with high school education. Based on the occupation, the majority of respondents are less knowledgeable than 18 respondents (60%) with the occupation of housewives. Based on information sources, the majority of respondents lack knowledge of 18 (60%) from electronic media. It can be concluded that the knowledge of women of childbearing age about breast self-examination is still lacking.